Philosophy of mathematics - Irvine, A. D. (Handbook of the Philosophy of Science, 2009)
Surveys historical and modern positions of mathematics. This book analyzes and evaluates traditional theories (Platonism, Aristotelianism, and Kantianism), and modern theories (logicism, formalism, constructivism, and factionalism). It discusses research in related fields (set theory, computability theory, probability theory, and par consistency)